Eksternalisasi Penerapan Hukuman Mati Terorisme dalam Perspektif Pidana Islam: Studi Komparasi Indonesia dan Mesir - Adelina, Riski; Zulkarnain (State of Islamic Institute Langsa, 2024)
As part of the global community, the death penalty for terrorism should ideally comply with international standards that respect human rights and justice. However, in Indonesia and Egypt, the implementation of the death penalty is often influenced by external and internal factors that deviate from these principles. This study aims to analyze how externalization affects the implementation of the death penalty for terrorism from the perspective of Islamic criminal law in Indonesia and Egypt. This article is classified as library research with a qualitative approach. The methodology used is a comparative study explained through descriptive analysis. The findings show that both countries are influenced by external pressures, with Indonesia experiencing tension between national policies and international standards, while Egypt struggles to balance Sharia principles with global demands. Although there are similarities in the impact of externalization, differences in implementation reflect the diversity of responses to international pressure within the context of Islamic criminal law.